Thermo-Reversible Sol-Gel Transition of Surface Modified Titanium Poly Oxo Building Blocks - Kaminski, Renata C. K. [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Judeinstein, Patrick; Meneau, Florian; Briois, Valerie; Santilli, Celso Valentim [UNESP] (Amer Chemical Soc, 2010)
In this paper, the thereto-reversible sol-gel transition of titanium poly oxo building blocks dispersed in a solution of p-toluene sulfonic acid (PTSH) in isopropanol is reported. The sol formed by the thereto-hydrolysis at 60 degrees C of titanium tetraisopropoxide (Ti((OPr)-Pr-i)(4)) reversibly changes into a gel upon cooling. A large domain of formulations (beta-domain) presenting this thereto-reversible behavior has been obtained for samples containing different nominal acidity (A = [PTSH]/[Ti]) and hydrolysis (H = [H2O]/[Ti]) ratios. The EXAFS study of the beta-domain evidences the formation of different titanium poly oxo building blocks, depending on the formulation, for which the local-order structure does not change upon sol-gel transition. This result points out that the thereto-reversible behavior is linked to interfacial properties of these building blocks. SAXS results indicate that the thereto-reversible gelation is associated to a reversible aggregation of a disperse set of building blocks. The presence of both immobilized and free PTSH species was revealed by Raman and H-1 NMR spectroscopies. Furthermore, NMR clearly evidences the significant decrease of free PTSH amount during the sol-gel transition. In the light of the different structural investigations, we propose that the thermo-reversible gelation is induced by the formation of a supramolecular network, in which the protonated surface of building blocks and/or aggregates are interconnected through cooperative bonds between the PTSH molecules.